The Influence of Bedding Planes and Permeability Coefficient on Fracture Propagation of Horizontal Wells in Stratification Shale Reservoirs. (6th February 2020) - Wang, Yuepeng; Liu, Xiangjun; Liang, Lixi; Xiong, Jian
Abstract : The complexity of hydraulic fractures (HF) significantly affects the success of reservoir reconstruction. The existence of a bedding plane (BP) in shale impacts the extension of a fracture. For shale reservoirs, in order to investigate the interaction mechanisms of HF and BPs under the action of coupled stress-flow, we simulate the processes of hydraulic fracturing under different conditions, such as the stress difference, permeability coefficients, BP angles, BP spacing, and BP mechanical properties using the rock failure process analysis code (RFPA 2D -Flow). Simulation results showed that HF spread outward around the borehole, while the permeability coefficient is uniformly distributed at the model without a BP or stress difference. The HF of the formation without a BP presented a pinnate distribution pattern, and the main direction of the extension is affected by both the ground stress and the permeability coefficient. When there is no stress difference in the model, the fracture extends along the direction of the larger permeability coefficient. In this study, the in situ stress has a greater influence on the extension direction of the main fracture when using the model with stress differences of 6 MPa. As the BP angle increases, the propagation of fractures gradually deviates from the BP direction. The initiation pressure and total breakdown pressure of the models at low permeability coefficients are higher than those under high permeability coefficients. In addition, the initiation pressure and total breakdown pressure of the models are also different. The larger the BP spacing, the higher the compressive strength of the BP, and a larger reduction ratio (the ratio of the strength parameters of the BP to the strength parameters of the matrix) leads to a smaller impact of the BP on fracture initiation and propagation. The elastic modulus has no effect on the failure mode of the model. When HF make contact with the BP, they tend to extend along the BP. Under the same in situ stress condition, the presence of a BP makes the morphology of HF more complex during the process of propagation, which makes it easier to achieve the purpose of stimulated reservoir volume (SRV) fracturing and increased production.